1996
DOI: 10.1007/s002130050149
|View full text |Cite
|
Sign up to set email alerts
|

Phenacetin O -deethylation by human liver microsomes in vitro: inhibition by chemical probes, SSRI antidepressants, nefazodone and venlafaxine

Abstract: Biotransformation of phenacetin via O-deethylation to acetaminophen, an index reaction reflecting activity of Cytochrome P450-1A2, was studied in microsomal preparations from a series of human livers. Acetaminophen formation was consistent with a double Michaelis-Menten system, with low-Km (mean Km1 = 68 microM) and high-Km (mean Km2 = 7691 microM) components. The low-K(m) enzyme accounted for an average of 96% of estimated intrinsic clearance, and was predicted to contribute more than 50% of net reaction velo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
54
0

Year Published

1998
1998
2019
2019

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 98 publications
(58 citation statements)
references
References 65 publications
4
54
0
Order By: Relevance
“…Apparent K m and V max values and intrinsic clearances (V max /K m ) for all substrates in human liver microsomes were in agreement with those found in previous studies (data not shown) (Leemann et al, 1993;Andersson et al, 1994;Bourrie et al, 1996;Li et al, 1997;Rendic and Di Carlo, 1997;von Moltke et al, 1997;Eagling et al, 1998). Kinetic analyses indicated that coumarin 7-hydroxylation, diclofenac 4Ј-hydroxylation, and omeprazole sulfoxidation were characterized by single-enzyme kinetics in human liver microsomes.…”
Section: Resultssupporting
confidence: 90%
“…Apparent K m and V max values and intrinsic clearances (V max /K m ) for all substrates in human liver microsomes were in agreement with those found in previous studies (data not shown) (Leemann et al, 1993;Andersson et al, 1994;Bourrie et al, 1996;Li et al, 1997;Rendic and Di Carlo, 1997;von Moltke et al, 1997;Eagling et al, 1998). Kinetic analyses indicated that coumarin 7-hydroxylation, diclofenac 4Ј-hydroxylation, and omeprazole sulfoxidation were characterized by single-enzyme kinetics in human liver microsomes.…”
Section: Resultssupporting
confidence: 90%
“…Chlorzoxazone hydroxylation was assayed following the method of Peter et al (1990). Phenacetin O-deethylation activity was determined using 25 M phenacetin, and the acetaminophen formation was analyzed by HPLC (Butler et al, 1989;von Moltke et al, 1996). Concentrations of substrates used in assays were 100 M AHH, 2 M EROD, 20 M MROD, 6 mM aniline hydroxylation, 200 M NFO, 2.5 mM tolbutamide hydroxylation, 500 M chlorzoxazone hydroxylation, and 25 M phenacetine O-deethylation.…”
Section: Methodsmentioning
confidence: 99%
“…Both 7-ethoxyresorufin and 7-methoxyresorufin were O-dealkylated mainly by CYP1A2 in human liver (Burke et al, 1994). In addition, human CYP1A2 is dominant in the O-deethylation of phenacetin at concentrations of Ͻ50 M (von Moltke et al, 1996). Thus, 25 M phenacetin was used in the determination of phenacetin O-deethylation activity of human liver microsomes.…”
Section: Assaymentioning
confidence: 99%
“…In addition, fluvoxamine, a potent inhibitor of CYP1A2, [46][47][48][49] increases the plasma concentration of typical antipsychotics (eg haloperidol), 50 further suggesting the involvement of CYP1A2 in antipsychotic metabolism. It should be noted that fluvoxamine can also inhibit other CYP enzymes (eg CYP2D6); 47 however, the in vitro inhibitory potency of fluvoxamine for CYP1A2 (K i = 0.24 M) 51 is approximately one order of magnitude greater than CYP2D6 (K i = 16.6 M) 52 and CYP3A4 (K i = 10.2 M). 52 Taken together, and considering the strong epidemiological association between smoking and schizophrenia, CYP1A2 can be viewed as another CYP (in addition to CYP2D6) which may contribute to disposition of typical antipsychotics in patients with schizophrenia during long-term treatment.…”
Section: Molecular Psychiatrymentioning
confidence: 99%